Outcome of endoscopy and barium radiography for acute upper gastrointestinal bleeding: controlled trial in 1037 patients. Issue 6315 (20th February 1982) - Dronfield, M W; Langman, M J; Atkinson, M; Balfour, T W; Bell, G D; Vellacott, K D; Amar, S S; Knapp, D R
Abstract : A study was conducted to find whether the higher diagnostic yield of endoscopy compared with barium radiography improves management or survival in patients with acute upper gastrointestinal bleeding. A total of 1037 patients were entered into a randomised study comparing the outcomes after each investigation. The diagnostic yield in patients who underwent endoscopy was 73% (382 of 526 cases) and in those examined by radiography 55% (280 of 511 cases). A fifth of the patients in the radiology group and a tenth of those in the endoscopy group subsequently underwent the alternative investigation; in most cases, however, no additional diagnostic information was obtained. Operation rates were similar in two groups, though patients in the endoscopy group were generally operated on sooner. Mortality rates were also similar in the two groups, though postoperative mortality was higher in the endoscopy group. Endoscopy may be a more accurate means of diagnosis than radiography, but it offers no short-term benefits in management.